Utility of metabolic screening in neurological presentations of infancy. Issue 7 (4th June 2020) - Djordjevic, Djurdja; Tsuchiya, Etsuko; Fitzpatrick, Megan; Sondheimer, Neal; Dowling, James J.
Abstract: Background: The first‐line use of specialized metabolic screening laboratories in the investigation of hypotonia and/or developmental delay remains a standard practice despite lack of supporting evidence. Our study aimed to address the utility of such testing by determining the proportion of patients whose diagnosis was directly supported by metabolic screening. Methods: We performed a retrospective chart review study of 164 patients under age one who had screening metabolic laboratory testing done within the time period of one calendar year. Results: Of patients screened, 9/164 (5.5%) had diagnoses supported by metabolic testing (two with nonketotic hyperglycinemia, three with ornithine transcarbamylase deficiency, one with propionic acidemia, one with a congenital disorder of glycosylation, one with D‐bifunctional protein deficiency, and one with GM1 Gangliosidosis). Of patients specifically evaluated for hypotonia and/or developmental delay, 5/79 (6.3%) were diagnosed with the aid of metabolic testing. All patients with positive screens presented with acute decompensation. Outside of this subgroup of high‐risk patients, no patients were diagnosed using metabolic testing. Screening laboratories were also ineffective in an outpatient setting, identifying only one of the seven outpatients who was ultimately diagnosed with an inborn error of metabolism. Conclusions: These findings demonstrate that the yield of specialized metabolic screening testing is extremely low in infants with hypotonia and/or developmental delay, approaching zero outside of the specific setting of clinical decompensation or multi‐system involvement. Furthermore, many outpatient cases of IEM are not identified by screening studies. This information will help guide the diagnostic evaluation of hypotonia and/or global developmental delay.